Pengaruh Urban Compactness terhadap Tingkat Ketersediaan Ruang Terbuka Hijau di Kawasan Solo Baru - Hasbi Asidiqi; Rizon Pamardhi Utomo; Soedwiwahjono Soedwiwahjono (ARSITEKTURA, 2017)
The development of city at this time tend to increase rapidly with the growing of built-up area as happened in Solo Baru Region. Then, appears compact city concept, The concept focuses on centralizing development in an area which is able to maximize the available land in the form of intensification of land use in a way that diverse land use in order to protect the environment (nature) vicinity of the possibility turned into urban areas. Meanwhile, urban compactness is a method for measuring how compact the region. This research was conducted by the administrative border of villages in Solo Baru Region. The problem in this research  how was the influence of urban compactness toward the level of green space availability in Solo Baru Region? The purpose of this study was to determine the influence of urban compactness toward the level of green space availability. Methods for determining urban compactness with assessing of three variables, namely the density, mixed-use and public transportation. While the level of availability of green space views based on availability to the population and territory. The method used the descriptive-quantitative analysis using scoring and descriptive-spasial. The results showed there is an influence on the level of urban compactness towards green space availability. The level of urban compactness influence on the green space availability was high in 2002 and also high in 2016. This research recommendations in the planning area is the availability of green space should be increased in prone compaction areas.Keywords: compact city, urban compactness, level of green space availibility